PENGEMBANGAN LITERASI KATABA UNTUK MENUNJANG PENDIDIKAN BERKUALITAS PERSPEKTIF QS. AL-‘ALAQ AYAT 1-5 - Hamidi, Ali; Syariful Anam, Muhammad; Fadlan Sidik, Firdan (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2021)
The Qur’an has a comprehensive view of the conception of education. Among the core of education is literacy. Student’s literacy skills are able to lead the nation’s generation to be literate and discover their potential. PISA research results in 2018 prove that Indonesia is ranked more than 10 and below in several assessment areas, such as reading, mathematics and science. The PISA 2018 data shows that the level of literacy in Indonesia is still low. Apart from the responsibility of the Ministry of Education and Culture (Kemdikbud) to develop educational policies, students also have a role as booster of the quality of education. Seeing the conception of literacy education from the perspective of the Qur’an, the KATABA Ma’had Al-Jami’ah became the object of research. The existence of this community acts as a support for the literacy atmosphere in the Ma’had environment which contributes to developing the world of writing and research. Through the qualitative method used in this study, the authors found that KATABA is a manifestation of the practice of the concept of literacy in Al-‘Alaq verses 1-5. The existence of literacy community among students contributes to the academic development of students. An increasing achievement index is one indicator of the success of the community in increasing the level of education in higher education.